Baby STRENGTH: Eat, Sleep, Console for Infants With Neonatal Abstinence Syndrome. (April 2021) - Miller, Patricia A.; Willier, Tina
Abstract : Background: Traditional medication-based management of neonatal abstinence syndrome (NAS) results in long hospitalizations. Nonpharmacologic treatment and using the Eat, Sleep, Console (ESC) model of care have been shown to decrease lengths of stay (LOSs). Purpose: To determine whether using the ESC model of care to treat infants with opioid withdrawal resulted in decreased LOSs and number of infants receiving morphine when compared with traditional medication management. Methods: Retrospective medical review for all patients admitted for NAS 12 months before and 12 months after implementing the ESC model of care. Data collected from electronic health records included demographic data, maternal history, infant LOS, infants receiving morphine, and birth weight/weight on day of life (DOL) 5. Univariate analysis was used to control for demographic data/risk factors. A 2-samples t test was used to compare average LOSs. Chi-square test was used to detect differences in the number of infants receiving morphine. Data were analyzed using SAS 9.4 software. Results: LOS decreased from mean of 17.7 days to a mean of 5.9 days ( P < .0001). The number of infants receiving morphine decreased from 20 (58.9%) to 1 (2.7%) ( P < .0001). No statistically significant difference was noted in the percentage of weight loss on DOL 5. Data showed an increase in breastfeeding rates from 41.18% to 64.86% ( P = .0456). Implications for Practice: The ESC model of care decreased infant LOS and the number of morphine doses administered for opioid withdrawal symptoms. Maternal breastfeeding rates increased. Implications for Research: More research is needed to determine long-term neurodevelopmental outcomes of infants managed using ESC principles.